Increases in the Macrolide Resistance of Mycoplasma genitalium and the Emergence of the A2058T Mutation in the 23S rRNA Gene: Clonal Spread? - Luis Piñeiro; Pedro Idigoras; Maitane Arrastia; Ayla Manzanal; Iñigo Ansa; Gustavo Cilla (MDPI AG, 2022)
The management of Mycoplasma genitalium sexually transmitted infection (STI) is hindered by increasing resistance to the recommended antibiotics, macrolides and quinolones, worldwide. In Gipuzkoa (Basque Country, Spain), macrolide and quinolone resistance rates in 2014-2018 were reported as <20% and <10%, respectively. The aims of this study were to compare these rates with those in 2019-2021 and analyse the genetic and epidemiological features of the strains and cases associated with striking changes in the resistance trends. Resistance to macrolides (n = 1019) and quinolones (n = 958) was studied, analysing mutations in 23S rRNA and parC/gyrA genes, respectively. The rate of macrolide resistance increased from 17.3% in 2014-2018 to 32.1% in 2019-2021, as much in the more prevalent A2058/2059G mutations (16.6-27.8%) as in the emergent A2058T mutations (0.5-4.1%) but with differences in the odds ratios and the relative risk increase between A2058T and A2058/2059G mutations. MG191 adhesin and MG309 lipoprotein of the 27 emergent strains detected with A2058T mutations were amplified, sequenced, and typed using phylogenetic and variable number tandem repeat analysis, respectively. Genetic clonal spread was ruled out, but most of the A2058T cases were men who had sex with men (24/27) with a history of STI and antibiotic treatments (19/27). No changes were observed in quinolone resistance trends, but the rate of resistance to both antibiotics rose from 2.9% to 8.3%, especially in cases with A2058T mutations. The genetic characterisation of strains and epidemiological surveillance of cases are needed to detect populations at increased risk of treatment failure in this infection.